The Revista Médica project: medical journals as instruments of German foreign cultural policy towards Latin America, 1920-1938 O projeto Revista Médica: periódicos médicos como instrumentos da política cultural externa alemã para a América Latina, 1920-1938 - Stefan Wulf (História, Ciências, Saúde: Manguinhos)
After the First World War, foreign cultural policy became one of the few fields in which Germany could act with relative freedom from the restrictions imposed by the Treaty of Versailles. In this context the Hamburg doctors Ludolph Brauer, Bernhard Nocht and Peter Mühlens created the Revista Médica de Hamburgo (as of 1928 Revista Médica Germano-Ibero-Americana), a monthly medical journal in Spanish (and occasionally in Portuguese), to increase German influence especially in Latin American countries. The focus of this article is on the protagonists of this project, the Hamburg doctors, the Foreign Office in Berlin, the German pharmaceutical industry, and the publishing houses involved. Depois da Primeira Guerra Mundial, a política cultural externa tornou-se um dos poucos campos em que a Alemanha podia atuar com relativa liberdade das restrições impostas pelo Tratado de Versalhes. Nesse contexto, os médicos Ludolph Brauer, Bernhard Nocht e Peter Mühlens, de Hamburgo, criaram a Revista Médica de Hamburgo (a partir de 1928 Revista Médica Germano-Ibero-Americana), um periódico mensal em espanhol (e ocasionalmente em português), para aumentar a influência alemã principalmente nos países da América Latina. O foco desse artigo são os protagonistas desse projeto: os médicos de Hamburgo, o Ministério das Relações Exteriores, a indústria farmacêutica alemã e as editoras.